Reflection of near-infrared light confers thermal protection in birds - Iliana Medina (Nature Portfolio, 2018)
More than half of solar radiation is at near-infrared (NIR) wavelengths. Here, Medina et al. show that among Australian birds NIR reflectivity is higher in species from hot, arid environments and their biophysical modelling further shows that this can reduce water loss from evaporative cooling.